The effects of Diet and corticosteroid-induced immune suppression during infection by Haemonchus contortus in lambs - Carvalho, Nadino [UNESP]; Neves, José Henrique das [UNESP]; Nazato, Carina; Louvandini, Helder; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B. V., 2015)
To evaluate the effects of Diet and corticosteroid-induced immune suppression during infection by Haemonchus contortus, 28 lambs were allocated to one of four groups treated as follows: Group Basal Diet - Normal; Group Basal Diet - Immune-Suppressed; Group Supplemented Diet - Normal; and Group Supplemented Diet - Immune-Suppressed. The Basal Diet contained Cynodon dactylon (cv. coast cross) hay with 82g crude protein (CP)/kg dry matter (DM), which was provided to the lambs in all groups ad libitum. In addition, animals on the Supplemented Diet received daily a commercial concentrate containing 171g CP/kg DM, which was offered in an amount corresponding to 3% of the animal's live weight. The Immune-Suppressed groups received treatments with the glucocorticoid methylprednisolone sodium succinate (1.33mg/kg of body weight), administered weekly. All lambs received a single infection with 4000 H. contortus infective larvae (L3) and were euthanised 28 days post-infection. Differences in pH and in the short-chain fatty acid (SCFA) concentrations occurred in rumen as a result of the distinct Diets offered to lambs. Such changes, however, did not have any apparent effect on larvae exsheathment and/or larvae survival inside the rumen, with all groups presenting similar worm burdens. However, animals on the Supplemented Diet presented reductions in worm growth and faecal egg counts. There was a significant effect of the Diet on the IgG levels against total antigens of H. contortus L3 from 7 to 27 days post-infection, with supplemented animals showing higher overall mean values (P<0.05). The immunosuppressive treatments had no effect on worm burden despite the reduction in the numbers of inflammatory cells in the abomasal mucosa of the Immune-Suppressed groups. These groups showed longer worms and females with more eggs in comparison with their counterparts fed each Diet; however, only the length of males was significantly affected (P<0.05). In conclusion, the changes caused in the rumen contents by supplementation with concentrate did not impair H. contortus establishment.
Keywords: Immunity; Nutrition; Sheep; Worm control